PENGARUH KUALITAS LAYANAN, NILAI PRODUK, KEPERCAYAAN TERHADAP NIAT UNTUK BERTRANSAKSI ULANG DENGAN KEPUASAN ANGGOTA SEBAGAI MEDIASI PADA KOSPIN “JASA” CABANG BATANG (Students' Journal of Economic and Management, 2014)
This study is a study that examines the effect of the service , product value and trust in the intentions to transact again with satisfaction as a member of the mediation services Kospin branch stems , to encourage members to transact ualang need to improve the quality of service , product value , trust and satisfaction of members . In this study , researchers used pusposive sampling and obtain a sample size of 100 sample members . Data from the questionnaire were then tested with test validity , The reliability , hypothesis , and multiple regression . The result variable service quality , product value and belief effect on customer satisfaction and service quality , product value and belief effect on intentions to transact again . Analisia further use mediation test vector that mediating variables influence the intention to transact again . The final conclusion of this study can be recommended as an input to management . Researchers believe bahawa kulaitas approach through service , product value , the trust will make members feel satisfied and will increase the members to transact again . This study has limitations that sampling periods were relatively short , not paying particular attention among variables and have not noticed any questions apkah known by members . Therefore, further studies are suggested to consider the time in the sampling periodandpay . Keywords : Quality Service, Product Value, Trust, Satisfaction and Intent Transaction Re- Member